Evaluation and comparison of apical bacterial extrusion after instrumentation of the root canals using various endodontic file systems: An in vitro study (Journal of Pharmaceutical Negative Results, 2022)
Aim: The purpose of this research is to compare the amounts of bacteria that are extruded from their apical surfaces during the instrumentation of root canals utilising the K3XF, Protaper Gold, Edge taper Platinum, and Hyflex CM Rotary systems.Materials and methods: Sixty caries free single rooted human maxillary incisor teeth were divided in six groups of ten teeth each. Teeth in each group were instrumented until the working length with the respective rotary file system. The access cavity was made, and the pulp and debris were removed from the canals. On the device for gathering microorganisms, the teeth were mounted. The Fusobacterium Nucleatum (ATCC 25586) was used to infect the root canals, which were then dried at 37 °C for 24 hours. Group I (Control group), no instrumentation was done. Group II used hand K-files, Group III used Protaper gold, Group IV used K3XF, Group V used Edge taper platinum, and Group VI used Hyflex CM rotary file systems. In. The sample was then collected, cultured in Mueller-Hinton agar for 24 hours, and the number of colony-forming units was counted.Statistical analysis: The Kruskal-Wallis nonparametric test and Mann-Whitney U test were applied to determine if significant differences existed among the groups ( P< 0.05)Results: Comparing hand K-files to the other four rotary systems, the K3XF file system extruded the fewer number of bacteria.Conclusion: Within the limitations of this study, it can be concluded that all instruments tested produced bacteria from intracanal spaces apically. However, compared to the manual method, engine-driven nickel-titanium devices extruded fewer microorganisms. Comparatively, the K3XF rotary file system extruded less microorganisms than other rotary file systems.